Encyclopedia of insects & arachnids - Burton, Maurice, 1898-1992; Burton, Robert, 1577-1640; Tweedie, Michael (London : Octopus Books, 1975)
Describes and illustrates the living conditions of insects, and arachnids, giving details of their life history, feeding habits and how they are equipped to protect themselves in the habitats.
Distributed in the United States by Crescent Books, New York.
Includes index.
Keywords: Arachnida -- Dictionaries; Bildband; Insects -- Dictionaries; Insekten; Spinnentiere; Wörterbuch